Role & Responsibility of Notaries as General Officers in Cooperative Registration through Online System - Muhammad Zulfa; Lathifah Hanim (Sultan Agung Notary Law Review, 2021)
The position of a Notary as a General Officer has the authority to make an Authentic Deed. Cooperative is a business entity which is a people's economic movement and is based on the principle of kinship. Since the promulgation of PP No. 24 of 2018, the management of business licensing in Indonesia will be carried out electronically, so it must have a Cooperative Establishment Deed which is made online by a Cooperative Deed Maker Notary, who must then obtain ratification of the Cooperative Establishment Deed. The objectives in this research include To find out and analyze the Cooperative Legal Entity Registration Procedure through the online system in Kudus Regency, To find out and analyze the role and responsibilities of a Notary in registering a Cooperative Legal Entity through the online system in Kudus Regency in case of data entry errors. To find out and analyze the legal consequences of the roles and responsibilities of a Notary in the event of an error in data entry. Based on the research concluded the role and responsibility of a Notary related to the establishment of a Cooperative is to assist in providing related counseling and draw up the Deed of Establishment of the Cooperative. After the deed of establishment, the Notary will register the ratification of the Deed of Establishment of the Cooperative through AHU Online, because without such ratification, business actors, in this case the Cooperative, cannot access OSS to administer business licenses.